anti-diradical formation in 1,3-dipolar cycloadditions of nitrile oxides to acetylenes - Haberhauer, Gebhard; Gleiter, Rolf; Woitschetzki, Sascha (The journal of organic chemistry, 2015)
By means of high level quantum chemical calculations (B2PLYPD and CCSD(T)), the mechanisms of the reaction of nitrile oxides with alkenes and alkynes were investigated. We were able to show that in the case of alkenes, regardless of the chosen substituents, the concerted mechanism is always energetically favored as compared to a two-step process, which runs through an anti-diradical species. In the case of alkynes, the concerted mechanism is favored only for the reaction of alkyl-substituted acetylenes. For aryl-substituted acetylenes, the activation barrier toward the anti-diradical is equal to or lower than the activation barrier of the concerted reaction. This reversal of the reaction paths is not only limited to nitrile oxides as dipolarophiles. Conditions favoring the anti-diradical path are the presence of a triple bond in both the 1,3-dipole and the dipolarophile and additionally an aryl substituent attached to the alkyne. The featured energy relationships between the reaction paths are able to explain the experimentally observed byproducts of the reaction of nitrile oxides with arylacetylenes. The discovered differences for the preferred reaction path of 1,3-dipolar cycloadditions to acetylenes should be of considerable interest to a broader field of chemists.
Gesehen am 22.02.2021